2021
DOI: 10.1111/cid.12992
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of early implant failure: A retrospective study of 6113 implants

Abstract: Background The risk factors of early implant failure were controversial among previous studies, especially for implants in different sites. Purpose To analyze the rate and risk factors of early implant failure occurring before the placement of final prosthesis. Materials and methods A retrospective study was conducted based on electrical medical records of patients who received dental implant placement from 2015 to 2019. Generalized estimation equation analyses were used to explore potential risk factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Bone implantation using nonliving materials (e.g., metals, polymers, and ceramics) as bone substitutes has proven to be an efficient clinical method for bone fracture fixation, joint arthroplasty, spinal reconstruction, and so on 1 3 . Clinically, the success rate of integration between implants and bone tissues exceeds 95% 4 , 5 , while the failure rate of early implantation was about 1.2% due to the development of fibrous tissue between the implants and the surrounding bone tissues in the healing period 6 . The general problem in these exogenous biomaterials is their bio-inertness, lacking in bioactivities to completely adapt to the complex physiological bone regeneration process.…”
Section: Introductionmentioning
confidence: 99%
“…Bone implantation using nonliving materials (e.g., metals, polymers, and ceramics) as bone substitutes has proven to be an efficient clinical method for bone fracture fixation, joint arthroplasty, spinal reconstruction, and so on 1 3 . Clinically, the success rate of integration between implants and bone tissues exceeds 95% 4 , 5 , while the failure rate of early implantation was about 1.2% due to the development of fibrous tissue between the implants and the surrounding bone tissues in the healing period 6 . The general problem in these exogenous biomaterials is their bio-inertness, lacking in bioactivities to completely adapt to the complex physiological bone regeneration process.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great progress in the development of new bioactive materials with accelerated osseointegration, the problem of a large number of implant rejections is still very relevant. A 5-year retrospective study (2015–2019) of 6113 dental implants indicated that the rate of failure is about 1.2% [ 9 ]. Most of these cases were caused by bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Data on peri‐implantitis related to the maxilla (5226 implants) and mandible (4370 implants) showed a higher prevalence in the maxilla (38.3%) than in the mandible (28.9%) 1,2,7,11–14,17,19,27,39,41 . Previous retrospective studies also observed a greater number of risk factors and probability of implant loss in the maxillary region 68,69 . Serino and Turri 70 found that 131 out of 264 patients with implants were diagnosed with peri‐implantitis.…”
Section: Prevalence Of Peri‐implantitis In Relation To the Implant Lo...mentioning
confidence: 99%
“…1,2,7,[11][12][13][14]17,19,27,39,41 Previous retrospective studies also observed a greater number of risk factors and probability of implant loss in the maxillary region. 68,69 Serino and Turri 70 found that 131 out of 264 patients with implants were diagnosed with peri-implantitis. Most of the implants associated with peri-implantitis were located in the maxilla, mainly in the anterior region.…”
Section: Maxilla and Mandiblementioning
confidence: 99%